Quantitative characterization of lateral force transmission in passive skeletal muscle - Bender, C. J.; Hawkins, M. S.; Hawkins, D. A. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Muscle-tendon research is critical for advancing preventative, surgical and rehabilitative techniques in orthopedic and sports medicine. Depending on architectural arrangements within individual muscles and between adjacent structures, a number of force transmission pathways are available. Traditionally, the myotendinous pathway is considered the exclusive means for muscular force transmission, but alternate pathways may employ intramuscular and intermuscular connective tissues to transmit force laterally (lateral force transmission, lft) (Huijing, et. al., 1998). Lateral force transmission was investigated in normal and partially compromised passive skeletal muscle systems in order to identify contributing factors and to quantify the fraction of total system force that can be transferred laterally.